Mackinawite partial oxidation to green rust produces a large, abiotic uranium isotope fractionation - Romain Guilbaud; Morten B. Andersen; Helen M. Freeman; Jeffrey Paulo H. Perez; David Uhlig; Liane G. Benning (Communications Earth & Environment)
Abstract Low-oxygen settings and transition zones between strictly anoxic and oxic conditions may have characterised large expanses of Precambrian continental margins, where oxygen-breathing, complex life emerged and diversified. Accurate reconstructions of oxygen levels in such conditions are therefore required, but current geochemical proxies fail in identifying transitional redox conditions. Uranium isotopes are an emerging palaeoredox proxy, as large isotope fractionations are recorded during the reduction of uranium into anoxic sediments. Their potential application to transitional conditions is, however, unclear, because the redox regulating mineralogy of such environments and the associated isotope fractionations are poorly constrained. Here, we explore the mineralogical transformations occurring during the partial oxidation of mackinawite. We show that green rust, a key mineral of Precambrian oceans, forms as a by-product of mackinawite oxidation, along with uraninite and polysulphide. We also demonstrate that this mechanism records a large abiotic uranium isotope fractionation during its reaction with aqueous iron sulphide.